The Use of Media Pictures in Learning Arabic Vocabulary in Elementary Schools - Pratiwi, Ranti; Al Rashid, Harun (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to describe the use of media pictures in learning Arabic vocabulary in elementary schools. This research is a qualitative type of field research at MIS Al-Hidayah Medan. The researcher obtained data on learning Arabic vocabulary using media pictures from data sources of Arabic class VI teachers at MIS Al-Hidayah Medan and documents supporting learning Arabic at the madrasah. Observation, interviews, and documentation carry out data collection techniques. At the same time, data analysis is done through data reduction, data presentation, and conclusion. The study results show that using media pictures to learn Arabic vocabulary at MIS Al-Hidayah is done by displaying images matching the Arabic vocabulary. The benefit of using media pictures during the learning process is that students can remember vocabulary and say it without referring to the book. The drawbacks of using media pictures are that the images used are not in the language, so students who sit behind will need help seeing the pictures displayed by the teacher.